AKAD FINANCING OF MURABAHAH BETWEEN CUSTOMERS WITH MUAMALAT BANKS HARKAT VIEWED FROM SHARI'AH PRINCIPLES - Candra Irawan; Adi Bastian; Febrozi Rohadi (Bengkoelen Justice : Jurnal Ilmu Hukum, 2020)
Currently in Indonesia Islamic Bank has gained a place and interested in the community, causing many emerging Syari'ah Bank and Financial Institutions of the syari'ah, and products in Islamic banks are widely used is murabahah financing. The formulation of the problem in this research are: (1). How is the implementation of the sale and purchase through murabahah financing between Bank Muamalat Harkat with customers. (2). Is trading system murabahah financing between Bank Muamalat Harkat and customers have been according to the principles of Syari’ah. (3). How murabahah financing efforts to resolve the breach between the customer and Muamalat Harkat. This research method is empirical legal research, this study was conducted in Bank Muamalat Harkat based data collection through field research such as interviews, observation and description as well as information from respondents through library research. The results of this research are: before an agreement Bank to assess carefully the prospective customer in the form of a comprehensive analysis and is divided into several stages, such as the assessment using the principle of 5C Character (Character of the debitor), Chapacity (Capability Candidate Debitor) , Capital (Capital candidate Debitor), Collateral (Collateral candidate Debitor) and Condition of economy (economic condition of the prospective Borrower). Trading system murabahah financing between Bank Muamalat Harkat with the customer has not fully based on the principles of the Syari'ah. Murabahah financing efforts to resolve the defaults can be solved by R3 is Restrukturing (Arrangement Back), Reconditioning (Terms Back) and Rescheduling (rescheduling), sales collateral and auction execution.